Correlation between adjuvant radiotherapy and high-risk basal cell carcinoma patients at Dr. Soetomo Surabaya General State Hospital - Larasati, Nikita Gladys; Sahudi, Sahudi; Wibowo, Marjono Dwi (Edelweiss Applied Science and Technology, 2025)
Basal Cell Carcinoma (BCC) is a malignant epithelial neoplasm of the skin primarily affecting individuals with lighter skin tones. Patients with high-risk BCC often require more intensive treatment for proper management. This comparative study uses a descriptive-analytic design with a retrospective cohort study approach. The study sample consisted of all patients diagnosed with BCC who underwent wide excision at Dr. Soetomo General Hospital from 2019 to 2022, meeting the inclusion and exclusion criteria, selected through purposive sampling. The results showed that 58% of all BCC patients who experienced recurrence were female, with 56% of them having undergone radiotherapy. In the non-recurrent BCC group, 80% of patients received radiotherapy, with the majority being female. This study concludes a significant association between adjuvant radiotherapy and recurrence in high-risk BCC patients at Dr. Soetomo General Hospital, Surabaya.